PENGEMBANGAN RENCANA PELAKSANAAN PEMBELAJARAN IPS BERORIENTASI HOTS, PADA MATERI TEMA 1 INDAHNYA KEBERSAMAAN KELAS 4 DI SEKOLAH DASAR - fitriani, fitriani (LPPM STKIP PGRI Bandar Lampung, 2019)
The formation of HOTS-oriented character education in elementary schools is a new breakthrough in developing student character. This study aims to shape the character of students and form higher-order thinking students related to social studies learning in SD. This study uses a HOTS-based learning development prototype model which refers to the Dick and Carry learning development model. The data collection techniques used were test and non-test techniques. The results of this study are expected to be able to contribute thoughts in social studies learning that triggers students to think at high levels so that it can show that the formation of HOTS-oriented student character education can be implemented in accordance with the target of learning achievement.